"I Thought It Was Normal:" Perspectives of Black Nursing Students From High-Risk IPV Communities on Causes and Solutions to IPV in the Black Community. Issue 13 (July 2022) - Vil, Noelle M. St.; Sperlich, Mickey; Fitzpatrick, Jessica; Bascug, Erin; Elliott, Jennifer
Black individuals are at high risk for intimate partner violence (IPV) but are less likely to utilize existing IPV services and supports. In an effort toward developing more culturally responsive IPV solutions for the Black community, researchers set out to understand how residents of high-risk IPV communities explained the high rates of IPV in their community, and what they thought possible solutions would entail. A purposive sample of 22 Black nursing students (20 female, 2 male) from a high-IPV risk predominately Black community in Western New York who were students enrolled in a Licensed Practitioner Nursing (LPN) program attended four focus groups that utilized a semi-structured interview format. Their verbatim responses were analyzed using qualitative inductive thematic analysis. Participants identified five major causes of IPV in Black communities: (a) weakened family structure, (b) IPV is normalized (c) community lacks IPV knowledge, (d) mistrust of formal resources, and (e) mental health. They also identified 10 solutions to IPV in Black communities: (a) counseling, (b) peer support groups, (c) use of technology, (d) resources to create self-sufficiency, (e) education, (f) culturally specific resources, (g) reduce stigma, (h) public service announcements, (i) substance abuse treatment, and (j) IPV screenings. Research and clinical implications of the research are discussed, including how these might inform the creation of culturally responsive interventions.